Study Finds Racism; Causes Black Americans and Asians Brain to Age Faster than of other Races, Increasing Dementia Risk - Tanveer Yousuf, Qurrat Ul Ain Shahid, Malik Muhammad Hamdan Tafheem, Marium Kanwal, Areeba Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This review aimed to find the racism and its effect on occurrence of dementia and treatment of dementia patients. It was observed that Asian and black American brain ages faster than the other races. Recent findings: The incidence of dementia or the ageing of brain was compared in different studies it was found that the black Americans and non-Hispanic white population had more cases of dementia as compared to white Americans. 2000 US consensus was taken as a standard and age adjusted incidence rate was calculated in different studies. In the general population the prevalence of dementia is higher among African American but lower among the Japanese American. The most recent studies of racial and ethnic difference in dementia incidence were limited to specific geographical areas. The well-known dementia is Traumatic brain injury (TBI), including mild TBI. The females veterans over 55 are particularly rise sharply in coming years. The ageing and dementia research community has identified different risk factors. The medical, lifestyle factors and genetic factors affect the dementia risk. The study discovered that blacks were 65 percent more likely than white Americans to develop dementia. The demographic factors like medical comorbidities, and psychiatric conditions are also have impact on dementia incidence. Summary: The study showed that the ageing of brain takes place early in case of non-white population as compared to white. The cases of dementia and the mortality rate of the patients are higher in case of non-white/black American. There is need to identify the factors that lead to this geographical distribution of disease. Keywords: dementia and Asian American adults.